Inversion-based set-point filter design for fractional control systems - Padula, Fabrizio; Visioli, A. (2014)
© 2014 IEEE.In this paper we propose a novel approach to design a set-point filter based on a dynamic inversion technique. First, a suitable command signal is designed in order to obtain a smooth monotonic output transition. Then, a set-point filter is determined based on the synthesized command signal. The filter is computed by minimizing the 2-norm difference between the command signal and the filter step response. The proposed approach is suitable for the design of two degree-of-freedom control systems because the set-point tracking performance is independent from the chosen feedback controller. Simulation results prove the effectiveness of the proposed methodology.